Evaporation-Induced Crystal Nucleation and Morphology of Dried Poly(Vinylidene Fluoride) Droplets - Yongri Liang; Susu Wang (Crystals, 2021)
The evaporation of a polymer solution droplet is important in solution-based polymer film fabrications, such as inkjet printing, spray coatings, and droplet casting, etc. In this work, we investigated the effect of droplet size, solvent evaporation rate, and concentration on the “coffee-ring” effect, crystal nucleation, polymorphism, and morphology of dried poly(vinylidene fluoride) (PVDF) solution droplets with the atomic force microscopy (AFM) and two-dimensional grazing incidence wide angle X-ray scattering (2D GIWAXS) method. We found that the crystal structure, morphology and crystal distribution in the center and edge regions of dried PVDF droplets were different due to the “coffee-ring” effect. The “coffee-ring” effect of dried PVDF droplets was mainly composited of accumulated crystals at the edge region of a droplet, which was mainly made by the crystallization of migrated chains. The interplay between the migration of chains and the crystallization and solidification of PVDF droplets significantly influenced the formation of the “coffee-ring”. In addition, our results showed that the decrease in droplet size and the controlling solvent evaporation rate were effective ways to improve the electroactive crystalline phases (β and γ-phases) nucleation and decrease the crystal size.